(3GdMeGjI GdLfGFjI ddeQCI (B:s (3OQGSI ebGQfI (B/ s - (3OYGA MSjf Ydj GdMOGOs; (3MSfjf EHQGgje UGdM YHjOs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B:s (3cdjI GdMbhb (B- (3LGeYI GdbGgQIs, 2023)
(3JYJHQ GdeQCI GdWQa GdCVYa HOfkqjG EPG eG bGQfGgG HZjQgG ef CaQGO GdCSQI; dPdc JbY YdjgG GdcKjQ ef GdLQGFe, GdCeQ GdPi jJWnqdH ef GdeTQY VQhQI GdJONd dMeGjJgG ci dG oJYoqO gOkaG SgkdG def jWeY HGdJYQV ddeQCI HPGJgG Ch MJi ddJYQV Edi MbhbgG(B. (3hdci fba HTcd LpqOi Ydi ehVhY GdOQGSI, dGHO ef GdJYQa Edi eNJda GdLQGFe GdJi JeS GdeQCI, ef NdGd Gdhbha YfO YfGUQ cd LQjeI Ydi MOI; MJi jecf EOQGc JhLgGJ GdeTQY GdeUQi(B. (3nhnJnJenqKd GdETncGdnqjI GdLhgQjI GdJi jWQMgG gPG GdehVhY ai(B: (3Edi Cpqi MmqO GSJWGY GdeTQY GdeUQi JhajQ MeGjI LfGFjI ddeQCI? hgd cad dgG GdMeGjI GdLfGFjI GdcGajI hGdefGSHI, HGYJHGQgG EfSGkfG hehGWkfG, hjQGYi NUhUjJgG ai Xd GdehGRfI Hjf GdGdJRGeGJ GdOhdjI hGdeHGOF hGdbje GdJi JMce GdeLJeY GdeUQi, Ce jJYnqjf aQV BdjGJ LOjOI dMeGjI GdeQCI ef cd CfhGY GdYfa ShGA bd Ch YXe, dJhGcH GdeJZjQGJ GdJi jTgOgG YUQfG GdMGdi, hgd ef Gdeecf eYGdLI GdKZQGJ GdbGfhfjI GdJi CNnqdJ ENdGkdG hGVkMG HeSCdI MeGjI GdeQCI LfGFkqjG? nhJHOh CgejI ehVhY gPg GdQSGdI ai Jbjje GdfUhU GdbGfhfjI GdeJYdbI HGdMeGjI GdLfGFjI ddeQCI, HJfGhd ChLg GdbUhQ GdJTQjYi, hcPdc ChLg GdJejjR GdeYjHI HjfgG hHjf GdQLd, afJYgO cnqd Pdc HGdJMdjd hGdfbO hUhkdG Edi GSJdgGe hVmY CeKd ddeQCI ai fUhU GdbGfhf GdLfGFi GdeUQi, Edi LGfH Pdc aEf GdehVhY jYO MjhkqjG ef MjK Enqf cKjkQG ef GdhbGFY GdLfGFjI GdeYQhVI ai SGMGJ GdbVGA JJYdb HeeGQSGJ GdYfa VO GdeQCI; hdPdc aEf fJGFL gPg GdQSGdI Jge GdeNGWHjf HCMcGe GdbGfhf GdLfGFi hGdbGFejf Ydi JfajPg(B..... (3EdN(B. s
The fundamental issue posed by this subject is: to what extent was the Egyptian legislature able to provide criminal protection to women? Has she been granted adequate and appropriate criminal protection, both as a human being and as a citizen? Respecting her privacy, in balancing international obligations with the principles and values that govern the Egyptian society, or should new mechanisms be imposed to protect women from all forms of violence, whether minor or major? In order to keep pace with the changes that are taking place in the current era, Would it be possible to address the legal gaps that have clearly violated the question of the criminal protection of women? The subject matter of this thesis appears to be important in assessing the legal provisions on the criminal protection of women by addressing the legislative shortcomings, as well as the flawed distinctions between women and men. We undertake to analyze and criticize all this in order to find an optimal position for women in Egyptian criminal law. Moreover, the subject is vital in that many of the criminal cases presented before the courts relate to violence against women; the results of this letter are therefore relevant to those who address and enforce the provisions of the Criminal Code.
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFj (B2023.s
(3HHdjhLQGajG(B: (3UaMGJ (B324-352.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdeQCIs; (3MeGjI GdeQCIs; (3GdYfa VOI GdeQCIs; (3GdJejjR VO GdeQCIs; (3ehGbYI GfKj HZjQ QVGgGs; (3GdOaGY Yf GdYQVs; (3LQjeI GdGZJUGH Yf WQjb GdGfJQfJs; (3gJc GdYQVs; (3GdaYd GdaGVMs; (3LQjeI GdJYQVs; (3LQjeI GdJMQT GdLfSjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs